FAKTOR YANG MEMPENGARUHI MINAT BERKUNJUNG MASYARAKAT PADA DESTINASI WISATA HALAL DI PROVINSI NUSA TENGGARA BARAT - Nisa, Khairun; Muttaqin, Aminnullah Achmad (Islamic Economics and finance in Focus, 2024)
Halal tourism is a new icon of tourism development that must be developed and requires attention, because it is expected to invite and attract tourists, both domestic and foreign tourists. The predicate of halal tourism or halal tourism is synonymous with the name West Nusa Tenggara, the potential for halal tourism owned by the province of NTB is very large. This study aims to determine the effect of perception, understanding and income on public interest in visiting halal tourist destinations in West Nusa Tenggara. This study uses quantitative research by collecting data through distributing questionnaires to 152 respondents. the data collected will be analyzed using Ordinal logistic Regression analysis. The results showed that the perception, understanding and income of the community had a positive and significant effect on the interest in visiting halal tourist destinations